2005
DOI: 10.1542/peds.2005-0487
|View full text |Cite
|
Sign up to set email alerts
|

Office Spirometry in Primary Care Pediatrics: A Pilot Study

Abstract: ABSTRACT. Objective. The aim of this study was to investigate the validity of office spirometry in primary care pediatric practices.Methods. Ten primary care pediatricians undertook a spirometry training program that was led by 2 pediatric pulmonologists from the Pediatric Department of the University of Padova. After the pediatricians' training, children with asthma or persistent cough underwent a spirometric test in the pediatrician's office and at a pulmonary function (PF) laboratory, in the same day in ran… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

3
26
0

Year Published

2008
2008
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 33 publications
(29 citation statements)
references
References 31 publications
3
26
0
Order By: Relevance
“…Our data suggest that pediatricians utilize spirometry to the greatest extent, and this is likely secondary to the past efforts to teach pediatricians about spirometry, how to utilize spirometry to optimize care of patients with asthma and how to interpret the results. 4,[6][7][8][9][10][11][12] While the usage of spirometry still seems low, our study shows increased frequency of its use over what has been demonstrated previously. This suggests that the NHLBI Guidelines for Management of Asthma have influenced care for patients with asthma.…”
Section: Dovepresssupporting
confidence: 55%
“…Our data suggest that pediatricians utilize spirometry to the greatest extent, and this is likely secondary to the past efforts to teach pediatricians about spirometry, how to utilize spirometry to optimize care of patients with asthma and how to interpret the results. 4,[6][7][8][9][10][11][12] While the usage of spirometry still seems low, our study shows increased frequency of its use over what has been demonstrated previously. This suggests that the NHLBI Guidelines for Management of Asthma have influenced care for patients with asthma.…”
Section: Dovepresssupporting
confidence: 55%
“…We attribute the low success of spirometry among the working children to their unfamiliarity with medical examinations, but also to the difficulty of performing spirometry in the field without visual control of the maneuvers. Other researchers have experienced similar difficulties (Zanconato 2005). In adults, poor spirometric performance may reflect poor respiratory health (Ng’Ang’a et al 1992).…”
Section: Discussionmentioning
confidence: 72%
“…1,2 The NAEPP guidelines emphasize the importance of preventive care on the basis of evidence-based principles, including (1) appropriate classification of asthma severity to initiate controller medications for persistent asthma symptoms, 3 (2) monitoring asthma control through repeated symptom assessments, [4][5][6][7] (3) education in conjunction with a written home asthma action/care plan (ACP) that guides self-management for asthma flares, [8][9][10] and (4) the use of primary care office spirometry as a tool for both diagnosis and monitoring asthma control. [11][12][13][14] We used a site-randomized trial design to determine if clinical decision support (CDS) embedded in an electronic health record (EHR) would improve clinician adherence to the NAEPP guidelines in the primary care setting. We hypothesized that this tool would help clinicians increase how often they prescribe controller medications for persistent asthma.…”
mentioning
confidence: 99%